Development of a Locally Loaded Early Childhood Language Curriculum Model Based on AI Technology to Improve Emergent Literacy - Harahap, Lia Andriani; Sudadio, Sudadio; Rusdiyani, Isti (Advances In Social Humanities Research, 2025)
The development of Early Childhood Education (ECE) curricula requires innovations that combine local wisdom with technological advancements. This study discusses creating early childhood language curricula based on local content and supported by Artificial Intelligence (AI) technology. The main goal is to develop a curriculum foundation that not only improves children's language skills but also promotes local cultural values through a modern approach. The method used includes a literature review and descriptive analysis of ECE curriculum practices in several educational institutions. The findings indicate that incorporating local content into an AI-based curriculum can enrich learning materials, support personalized language learning, and boost children's motivation via interactive and contextual media. However, successful implementation depends on educators' readiness, technological infrastructure, and supportive regulations. This study concludes that an early childhood language curriculum based on local content and enhanced by AI offers an innovative strategy to meet future digital-era challenges while maintaining cultural identity.